High-temperature-resistant BOPP film for copper-clad plate and preparation method thereof
By performing light treatment and specific chemical treatment on the BOPP film, the problem of melting and sticking to steel plates at high temperatures is solved, and its thermal stability and flame retardant properties are improved.
Patent Information
- Application Number
- CN202411825938.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-14
AI Technical Summary
The existing BOPP film is prone to melt due to high temperature during the pressing process of CEM-1 single-sided copper clad plate, which increases production costs, and the phenomenon of sticking steel plates is serious.
By illuminating the BOPP film, including immersion in aqueous ammonium sulfate solution and irradiation with ultraviolet light, followed by treatment with allyl dimethyl phosphate and polydimethyl methylhydrosiloxane, a denser structure is formed and phosphorus elements are introduced to improve flame retardant properties.
It improves the tensile and thermal stability of the BOPP film, avoids the phenomenon of sticking to steel plates, and enhances the flame retardant performance, so that it can be used stably at higher temperatures.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a high-temperature resistant BOPP film for copper-clad laminates. Background Art
[0002] Biaxially oriented polypropylene film is referred to as BOPP, which is generally a multi-layer co-extruded film. This film has high tensile strength, impact strength, rigidity, toughness and good transparency. It is colorless, odorless, tasteless, non-toxic, and has excellent physical and mechanical properties and chemical stability. It is a widely used film. In the lamination process of CEM-1 single-sided copper clad laminate, BOPP film plays an isolating role. Regarding the lamination temperature and pressure of the substrate, the product characteristics and parameters of each substrate manufacturer are different. If the lamination temperature is too high, BOPP will melt and adhere to the steel plate, increasing the production cost. Therefore, it is necessary to improve the stability of BOPP film to improve the phenomenon of BOPP film sticking to the steel plate. Summary of the invention
[0003] The object of the present invention is to provide a high temperature resistant BOPP film for copper clad laminate and a preparation method thereof, so as to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: A high temperature resistant BOPP film for copper clad laminates is prepared by subjecting a BOPP film to light treatment and then sequentially treating the film with a primary treatment liquid and a secondary treatment liquid.
[0005] As an optimization, the light treatment is to wash the BOPP film and immerse it in an aqueous solution of ammonium sulfate, take it out and irradiate the surface with ultraviolet light, then take it out by immersion, irradiate the other side with ultraviolet light, and finally soak it in water.
[0006] As an optimization, the primary treatment liquid is prepared by uniformly mixing allyl dimethyl phosphate and anhydrous ethanol; the secondary treatment liquid is prepared by uniformly mixing polydimethylmethylhydrogensiloxane, chloroplatinic acid and n-hexane.
[0007] A method for preparing a high temperature resistant BOPP film for a copper clad laminate comprises the following preparation steps: (1) Light treatment: The BOPP film was ultrasonically cleaned with pure water and anhydrous ethanol for 10-15 min in sequence, and dried at 60-70°C for 3-4 h to obtain the cleaned BOPP film. The cleaned BOPP film was immersed in an aqueous solution of ammonium persulfate with a mass fraction of 20%-30%, and taken out after standing for 10 min. The film was drained until no liquid droplets fell for 5 s, spread flat and subjected to ultraviolet irradiation, and immersed in an aqueous solution of ammonium persulfate with a mass fraction of 20%-30% again. The film was taken out after standing for 10 min, and drained until no liquid droplets fell for 5 s. The film that had not been subjected to ultraviolet irradiation was subjected to the same ultraviolet irradiation, and ultrasonically cleaned with pure water and anhydrous ethanol for 10-15 min in sequence, and then immersed in pure water at 40-50°C for 16-20 h. The film was taken out and dried at 60-70°C for 6-8 h to obtain the BOPP film after light treatment. (2) Primary treatment: The light-treated BOPP film was immersed in the primary treatment liquid and allowed to stand for 30 to 60 minutes. The film was taken out and drained until no liquid dripped for 5 seconds. The film was placed in a muffle furnace for heating treatment. The film was kept at 70 to 80°C for 20 to 30 minutes, 100 to 110°C for 20 to 30 minutes, and 140 to 150°C for 50 to 60 minutes. After cooling to room temperature, the film was immersed in the primary treatment liquid and then placed in a muffle furnace for heating treatment for three times. After cooling to room temperature, the film was ultrasonically cleaned with pure water and acetone for 10 to 15 minutes, and dried at 60 to 70°C for 6 to 8 hours to obtain a BOPP film after primary treatment. (3) Secondary treatment: Immerse the BOPP film after the primary treatment in the secondary treatment solution and let it stand for 10-15 minutes, take it out and drain it until no liquid drops for 5 seconds, let it stand at 70-80℃ for 30-40 minutes, cool it to room temperature, and then repeat the process of immersing it in the secondary treatment solution and letting it stand at 70-80℃ for 30-40 minutes for three times. After cooling to room temperature, ultrasonically clean it with pure water and acetone for 10-15 minutes in turn, and dry it at 60-70℃ for 6-8 hours to obtain a high-temperature resistant BOPP film for copper clad laminate.
[0008] As an optimization, the BOPP film thickness in step (1) is 50 μm, and the manufacturer is Jiangsu Sanjiajiu New Material Technology Co., Ltd.
[0009] As an optimization, the process parameters of the ultraviolet irradiation in step (1) are: ultraviolet wavelength 254nm, light intensity 9000μw / cm 2 , illumination time 2min.
[0010] As an optimization, the primary treatment liquid in step (2) is prepared by uniformly mixing allyl dimethyl phosphate and anhydrous ethanol in a mass ratio of 1:4-6.
[0011] As an optimization, the secondary treatment liquid in step (3) is prepared by uniformly mixing polydimethylmethylhydrogensiloxane, chloroplatinic acid and n-hexane in a mass ratio of 1:0.02~0.03:6~8.
[0012] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the high-temperature resistant BOPP film for copper-clad laminates, the BOPP film is washed and immersed in an ammonium sulfate aqueous solution, taken out and the surface is irradiated with ultraviolet light, then taken out by immersion, the other side is irradiated with ultraviolet light, and finally immersed in water to obtain the light-treated BOPP film, and then treated with allyl dimethyl phosphate and polydimethylmethylhydrogensiloxane in sequence to obtain the high-temperature resistant BOPP film for copper-clad laminates.
[0013] First, the surface of the BOPP film is irradiated with ultraviolet light and immersed in water to make the BOPP film after light treatment contain a large number of hydroxyl groups. Then it is treated with allyl dimethyl phosphate. Allyl dimethyl phosphate reacts with the hydroxyl groups on the BOPP film after light treatment through an ester exchange reaction, so that the different molecular chains of the BOPP film after light treatment are cross-linked with each other, making the structure denser, thereby improving the tensile properties and thermal stability. At the same time, the introduced phosphorus element can improve the flame retardant properties.
[0014] Secondly, it is treated with polydimethylmethylhydrogensiloxane, which can be bonded to the surface of the BOPP film through a hydrosilylation reaction, thereby improving the overall thermal stability and protecting the internal polypropylene molecular chains, so that it will not stick to the steel plate at a higher temperature. It can also cross-link the double bonds on different molecular chains to further improve the tensile properties. At the same time, it can coordinate with the phosphorus element to achieve flame retardancy and improve the flame retardant effect. DETAILED DESCRIPTION
[0015] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] In order to more clearly illustrate the method provided by the present invention, the following examples are described in detail. Example 1
[0017] A method for preparing a high temperature resistant BOPP film for a copper clad laminate, the method for preparing a high temperature resistant BOPP film for a copper clad laminate mainly comprising the following preparation steps: (1) Light treatment: The BOPP film was ultrasonically cleaned with pure water and anhydrous ethanol for 10 min in sequence, and dried at 60 °C for 4 h to obtain the cleaned BOPP film. The cleaned BOPP film was immersed in an aqueous solution of ammonium persulfate with a mass fraction of 20% to 30%, and then taken out after standing for 10 min. The film was drained until no liquid droplets fell for 5 s, and then spread flat and irradiated with ultraviolet light at a wavelength of 254 nm and a light intensity of 9000 μw / cm 2 , the light exposure time is 2 minutes, and it is immersed in a 20% by mass ammonium persulfate aqueous solution again, and it is taken out after standing for 10 minutes, and it is taken out and drained until no liquid drops fall for 5 seconds, and the same ultraviolet irradiation is performed on the film that has not been subjected to ultraviolet irradiation, and it is ultrasonically cleaned with pure water and anhydrous ethanol for 10 minutes in turn, and then it is immersed in 40℃ pure water for 20 hours, and it is taken out and dried at 60℃ for 8 hours to obtain a BOPP film after light treatment; (2) Primary treatment: allyl dimethyl phosphate and anhydrous ethanol were mixed in a mass ratio of 1:4 to prepare a primary treatment solution; the BOPP film after light treatment was immersed in the primary treatment solution and allowed to stand for 30 minutes, taken out and drained until no liquid dripped for 5 seconds, placed in a muffle furnace for heating treatment, and kept at 70°C for 20 minutes, 100°C for 30 minutes, and 140°C for 60 minutes in sequence. After cooling to room temperature, the film was immersed in the primary treatment solution and placed in a muffle furnace for heating treatment for 3 times. After cooling to room temperature, it was ultrasonically cleaned with pure water and acetone for 10 minutes in sequence, and dried at 60°C for 8 hours to obtain a BOPP film after primary treatment; (3) Secondary treatment: Polydimethylmethylhydrogensiloxane, chloroplatinic acid and n-hexane are mixed in a mass ratio of 1:0.02:6 to prepare a secondary treatment solution; the BOPP film after the primary treatment is immersed in the secondary treatment solution and allowed to stand for 10 min, taken out and drained until no liquid drops for 5 s, allowed to stand at 70 °C for 40 min, cooled to room temperature, and then immersed in the secondary treatment solution and allowed to stand at 70 °C for 40 min three times. After cooling to room temperature, it is ultrasonically cleaned with pure water and acetone for 10 min in turn, and dried at 70 °C for 6 h to obtain a high temperature resistant BOPP film for copper clad laminate. Example 2
[0018] A method for preparing a high temperature resistant BOPP film for a copper clad laminate, the method for preparing a high temperature resistant BOPP film for a copper clad laminate mainly comprising the following preparation steps: (1) Light treatment: The BOPP film was ultrasonically cleaned with pure water and anhydrous ethanol for 12 min in sequence, and dried at 60-70 °C for 3.5 h to obtain the cleaned BOPP film. The cleaned BOPP film was immersed in a 25% by mass ammonium persulfate aqueous solution, allowed to stand for 10 min, and then taken out and drained until no liquid dripped for 5 s. The film was then laid flat and irradiated with ultraviolet light at a wavelength of 254 nm and a light intensity of 9000 μw / cm 2, the light exposure time is 2 minutes, and it is immersed in a 25% by mass ammonium persulfate aqueous solution again, and it is taken out after standing for 10 minutes, and it is taken out and drained until no liquid drops fall for 5 seconds, and the same ultraviolet irradiation is performed on the film that has not been subjected to ultraviolet irradiation, and it is ultrasonically cleaned with pure water and anhydrous ethanol for 12 minutes in sequence, and then it is immersed in 45℃ pure water for 18 hours, and it is taken out and dried at 65℃ for 7 hours to obtain a BOPP film after light treatment; (2) Primary treatment: Allyl dimethyl phosphate and anhydrous ethanol were mixed in a mass ratio of 1:5 to prepare a primary treatment solution; the light-treated BOPP film was immersed in the primary treatment solution and allowed to stand for 30 min, taken out and drained until no liquid dripped for 5 s, placed in a muffle furnace for heating treatment, and kept at 75°C for 25 min, 105°C for 25 min, and 145°C for 55 min in sequence. After cooling to room temperature, the film was immersed in the primary treatment solution and then placed in a muffle furnace for heating treatment for 3 times. After cooling to room temperature, the film was ultrasonically cleaned with pure water and acetone for 12 min in sequence, and dried at 65°C for 7 h to obtain a BOPP film after primary treatment; (3) Secondary treatment: Polydimethylmethylhydrogensiloxane, chloroplatinic acid and n-hexane were mixed in a mass ratio of 1:0.025:7 to prepare a secondary treatment solution; the BOPP film after the primary treatment was immersed in the secondary treatment solution and allowed to stand for 12 min, taken out and drained until no liquid dripped for 5 s, allowed to stand at 75 °C for 35 min, cooled to room temperature, and then immersed in the secondary treatment solution and allowed to stand at 75 °C for 35 min three times. After cooling to room temperature, it was ultrasonically cleaned with pure water and acetone for 12 min in turn, and dried at 65 °C for 7 h to obtain a high temperature resistant BOPP film for copper clad laminate. Example 3
[0019] A method for preparing a high temperature resistant BOPP film for a copper clad laminate, the method for preparing a high temperature resistant BOPP film for a copper clad laminate mainly comprising the following preparation steps: (1) Light treatment: The BOPP film was ultrasonically cleaned with pure water and anhydrous ethanol for 15 min in sequence, and dried at 70 °C for 3 h to obtain the cleaned BOPP film. The cleaned BOPP film was immersed in a 30% by mass ammonium persulfate aqueous solution, left to stand for 10 min, and then taken out and drained until no liquid dripped for 5 s. The film was then laid flat and irradiated with ultraviolet light at a wavelength of 254 nm and a light intensity of 9000 μw / cm 2 , the light exposure time is 2 minutes, and it is immersed in a 30% by mass fraction ammonium persulfate aqueous solution again, and it is taken out after standing for 10 minutes, and it is taken out and drained until no liquid drops fall for 5 seconds, and the same ultraviolet irradiation is performed on the film that has not been subjected to ultraviolet irradiation, and it is ultrasonically cleaned with pure water and anhydrous ethanol for 15 minutes in sequence, and then it is immersed in 40-50 ℃ pure water for 16 hours, and it is taken out and dried at 60-70 ℃ for 6-8 hours to obtain a BOPP film after light treatment; (2) Primary treatment: Allyl dimethyl phosphate and anhydrous ethanol were mixed in a mass ratio of 1:6 to prepare a primary treatment solution; the light-treated BOPP film was immersed in the primary treatment solution and allowed to stand for 60 min, taken out and drained until no liquid dripped for 5 s, placed in a muffle furnace for heating treatment, and kept at 80°C for 20 min, 110°C for 20 min, and 150°C for 50 min in sequence. After cooling to room temperature, the film was immersed in the primary treatment solution and then placed in a muffle furnace for heating treatment for 3 times. After cooling to room temperature, the film was ultrasonically cleaned with pure water and acetone for 15 min in sequence, and dried at 70°C for 6 h to obtain a BOPP film after primary treatment; (3) Secondary treatment: Polydimethylmethylhydrogensiloxane, chloroplatinic acid and n-hexane were mixed in a mass ratio of 1:0.03:8 to prepare a secondary treatment solution; the BOPP film after the primary treatment was immersed in the secondary treatment solution and allowed to stand for 15 min, taken out and drained until no liquid dripped for 5 s, allowed to stand at 80 °C for 30 min, cooled to room temperature, and then immersed in the secondary treatment solution and allowed to stand at 80 °C for 30 min for 3 times. After cooling to room temperature, it was ultrasonically cleaned with pure water and acetone for 15 min in turn, and dried at 70 °C for 6 h to obtain a high temperature resistant BOPP film for copper clad laminate.
[0020] Comparative Example 1 A method for preparing a high temperature resistant BOPP film for a copper clad laminate, the method for preparing a high temperature resistant BOPP film for a copper clad laminate mainly comprising the following preparation steps: (1) Light treatment: The BOPP film was ultrasonically cleaned with pure water and anhydrous ethanol for 12 min in sequence, and dried at 60-70 °C for 3.5 h to obtain the cleaned BOPP film. The cleaned BOPP film was immersed in a 25% by mass ammonium persulfate aqueous solution, allowed to stand for 10 min, and then taken out and drained until no liquid dripped for 5 s. The film was then laid flat and irradiated with ultraviolet light at a wavelength of 254 nm and a light intensity of 9000 μw / cm 2 , the light exposure time is 2 minutes, and it is immersed in a 25% by mass ammonium persulfate aqueous solution again, and it is taken out after standing for 10 minutes, and it is taken out and drained until no liquid drops fall for 5 seconds, and the same ultraviolet irradiation is performed on the film that has not been subjected to ultraviolet irradiation, and it is ultrasonically cleaned with pure water and anhydrous ethanol for 12 minutes in sequence, and then it is immersed in 45℃ pure water for 18 hours, and it is taken out and dried at 65℃ for 7 hours to obtain a BOPP film after light treatment; (2) Primary treatment: Ethyl acrylate and anhydrous ethanol were mixed in a mass ratio of 1:5 to prepare a primary treatment solution; the light-treated BOPP film was immersed in the primary treatment solution and allowed to stand for 30 min, taken out and drained until no liquid dripped for 5 s, placed in a muffle furnace for heating treatment, and kept at 75°C for 25 min, 105°C for 25 min, and 145°C for 55 min in sequence. After cooling to room temperature, the film was immersed in the primary treatment solution and then placed in a muffle furnace for heating treatment for 3 times. After cooling to room temperature, the film was ultrasonically cleaned with pure water and acetone for 12 min in sequence, and dried at 65°C for 7 h to obtain a BOPP film after primary treatment; (3) Secondary treatment: Polydimethylmethylhydrogensiloxane, chloroplatinic acid and n-hexane were mixed in a mass ratio of 1:0.025:7 to prepare a secondary treatment solution; the BOPP film after the primary treatment was immersed in the secondary treatment solution and allowed to stand for 12 min, taken out and drained until no liquid dripped for 5 s, allowed to stand at 75 °C for 35 min, cooled to room temperature, and then immersed in the secondary treatment solution and allowed to stand at 75 °C for 35 min three times. After cooling to room temperature, it was ultrasonically cleaned with pure water and acetone for 12 min in turn, and dried at 65 °C for 7 h to obtain a high temperature resistant BOPP film for copper clad laminate.
[0021] Comparative Example 2 A method for preparing a high temperature resistant BOPP film for a copper clad laminate, the method for preparing a high temperature resistant BOPP film for a copper clad laminate mainly comprising the following preparation steps: (1) Light treatment: The BOPP film was ultrasonically cleaned with pure water and anhydrous ethanol for 12 min in sequence, and dried at 60-70 °C for 3.5 h to obtain the cleaned BOPP film. The cleaned BOPP film was immersed in a 25% by mass ammonium persulfate aqueous solution, allowed to stand for 10 min, and then taken out and drained until no liquid dripped for 5 s. The film was then laid flat and irradiated with ultraviolet light at a wavelength of 254 nm and a light intensity of 9000 μw / cm 2 , the light exposure time is 2 minutes, and it is immersed in a 25% by mass ammonium persulfate aqueous solution again, and it is taken out after standing for 10 minutes, and it is taken out and drained until no liquid drops fall for 5 seconds, and the same ultraviolet irradiation is performed on the film that has not been subjected to ultraviolet irradiation, and it is ultrasonically cleaned with pure water and anhydrous ethanol for 12 minutes in sequence, and then it is immersed in 45℃ pure water for 18 hours, and it is taken out and dried at 65℃ for 7 hours to obtain a BOPP film after light treatment; (2) Primary treatment: diethyl maleate and anhydrous ethanol were mixed in a mass ratio of 1:5 to prepare a primary treatment solution; the light-treated BOPP film was immersed in the primary treatment solution and allowed to stand for 30 min, taken out and drained until no liquid dripped for 5 s, placed in a muffle furnace for heating treatment, and kept at 75°C for 25 min, 105°C for 25 min, and 145°C for 55 min in sequence. After cooling to room temperature, the film was immersed in the primary treatment solution and then placed in a muffle furnace for heating treatment for 3 times. After cooling to room temperature, the film was ultrasonically cleaned with pure water and acetone for 12 min in sequence, and dried at 65°C for 7 h to obtain a BOPP film after primary treatment; (3) Secondary treatment: Polydimethylmethylhydrogensiloxane, chloroplatinic acid and n-hexane were mixed in a mass ratio of 1:0.025:7 to prepare a secondary treatment solution; the BOPP film after the primary treatment was immersed in the secondary treatment solution and allowed to stand for 12 min, taken out and drained until no liquid dripped for 5 s, allowed to stand at 75 °C for 35 min, cooled to room temperature, and then immersed in the secondary treatment solution and allowed to stand at 75 °C for 35 min three times. After cooling to room temperature, it was ultrasonically cleaned with pure water and acetone for 12 min in turn, and dried at 65 °C for 7 h to obtain a high temperature resistant BOPP film for copper clad laminate.
[0022] Comparative Example 3 A method for preparing a high temperature resistant BOPP film for a copper clad laminate, the method for preparing a high temperature resistant BOPP film for a copper clad laminate mainly comprising the following preparation steps: (1) Light treatment: The BOPP film was ultrasonically cleaned with pure water and anhydrous ethanol for 12 min in sequence, and dried at 60-70 °C for 3.5 h to obtain the cleaned BOPP film. The cleaned BOPP film was immersed in a 25% by mass ammonium persulfate aqueous solution, allowed to stand for 10 min, and then taken out and drained until no liquid dripped for 5 s. The film was then laid flat and irradiated with ultraviolet light at a wavelength of 254 nm and a light intensity of 9000 μw / cm 2 , the light exposure time is 2 minutes, and it is immersed in a 25% by mass ammonium persulfate aqueous solution again, and it is taken out after standing for 10 minutes, and it is taken out and drained until no liquid drops fall for 5 seconds, and the same ultraviolet irradiation is performed on the film that has not been subjected to ultraviolet irradiation, and it is ultrasonically cleaned with pure water and anhydrous ethanol for 12 minutes in sequence, and then it is immersed in 45℃ pure water for 18 hours, and it is taken out and dried at 65℃ for 7 hours to obtain a BOPP film after light treatment; (2) Post-treatment: Allyl dimethyl phosphate and anhydrous ethanol were mixed in a mass ratio of 1:5 to prepare a primary treatment solution; the light-treated BOPP film was immersed in the primary treatment solution and allowed to stand for 30 min, taken out and drained until no liquid dripped for 5 s, placed in a muffle furnace for heating treatment, and kept at 75°C for 25 min, 105°C for 25 min, and 145°C for 55 min in sequence. After cooling to room temperature, the film was immersed in the primary treatment solution and then placed in a muffle furnace for heating treatment for 3 times. After cooling to room temperature, the film was ultrasonically cleaned with pure water and acetone for 12 min in sequence, and dried at 65°C for 7 h to obtain a high-temperature resistant BOPP film for copper clad laminate.
[0023] Comparative Example 4 A method for preparing a high temperature resistant BOPP film for a copper clad laminate, the method for preparing a high temperature resistant BOPP film for a copper clad laminate mainly comprising the following preparation steps: (1) Light treatment: The BOPP film was ultrasonically cleaned with pure water and anhydrous ethanol for 12 min in sequence, and dried at 60-70 °C for 3.5 h to obtain the cleaned BOPP film. The cleaned BOPP film was immersed in a 25% by mass ammonium persulfate aqueous solution, allowed to stand for 10 min, and then taken out and drained until no liquid dripped for 5 s. The film was then laid flat and irradiated with ultraviolet light at a wavelength of 254 nm and a light intensity of 9000 μw / cm 2 , the light exposure time is 2 minutes, and it is immersed in a 25% by mass ammonium persulfate aqueous solution again, and it is taken out after standing for 10 minutes, and it is taken out and drained until no liquid drops fall for 5 seconds, and the same ultraviolet irradiation is performed on the film that has not been subjected to ultraviolet irradiation, and it is ultrasonically cleaned with pure water and anhydrous ethanol for 12 minutes in sequence, and then it is immersed in 45℃ pure water for 18 hours, and it is taken out and dried at 65℃ for 7 hours to obtain a BOPP film after light treatment; (2) Post-treatment: Ethyl acrylate and anhydrous ethanol were mixed in a mass ratio of 1:5 to prepare a primary treatment solution; the light-treated BOPP film was immersed in the primary treatment solution and allowed to stand for 30 min, taken out and drained until no liquid dripped for 5 s, and placed in a muffle furnace for heating treatment, and kept at 75°C for 25 min, 105°C for 25 min, and 145°C for 55 min in sequence. After cooling to room temperature, the film was immersed in the primary treatment solution and then placed in a muffle furnace for heating treatment for 3 times. After cooling to room temperature, the film was ultrasonically cleaned with pure water and acetone for 12 min in sequence, and dried at 65°C for 7 h to obtain a high-temperature resistant BOPP film for copper clad laminate.
[0024] Comparative Example 5 A method for preparing a high temperature resistant BOPP film for a copper clad laminate, the method for preparing a high temperature resistant BOPP film for a copper clad laminate mainly comprising the following preparation steps: (1) Light treatment: The BOPP film was ultrasonically cleaned with pure water and anhydrous ethanol for 12 min in sequence, and dried at 60-70 °C for 3.5 h to obtain the cleaned BOPP film. The cleaned BOPP film was immersed in a 25% by mass ammonium persulfate aqueous solution, allowed to stand for 10 min, and then taken out and drained until no liquid dripped for 5 s. The film was then laid flat and irradiated with ultraviolet light at a wavelength of 254 nm and a light intensity of 9000 μw / cm 2 , the light exposure time is 2 minutes, and it is immersed in a 25% by mass ammonium persulfate aqueous solution again, and it is taken out after standing for 10 minutes, and it is taken out and drained until no liquid drops fall for 5 seconds, and the same ultraviolet irradiation is performed on the film that has not been subjected to ultraviolet irradiation, and it is ultrasonically cleaned with pure water and anhydrous ethanol for 12 minutes in sequence, and then it is immersed in 45℃ pure water for 18 hours, and it is taken out and dried at 65℃ for 7 hours to obtain a BOPP film after light treatment; (2) Post-treatment: Diethyl maleate and anhydrous ethanol were mixed in a mass ratio of 1:5 to prepare a primary treatment solution; the light-treated BOPP film was immersed in the primary treatment solution and allowed to stand for 30 min, taken out and drained until no liquid dripped for 5 s, placed in a muffle furnace for heating treatment, and kept at 75°C for 25 min, 105°C for 25 min, and 145°C for 55 min in sequence. After cooling to room temperature, the film was immersed in the primary treatment solution and then placed in a muffle furnace for heating treatment for 3 times. After cooling to room temperature, the film was ultrasonically cleaned with pure water and acetone for 12 min in sequence, and dried at 65°C for 7 h to obtain a high-temperature resistant BOPP film for copper clad laminate.
[0025] Test Example 1 Test for the presence or absence of steel plate sticking The high temperature resistant BOPP films for copper clad laminate obtained in the comparative examples of the embodiments were placed in a hot press for hot pressing at a pressure of 38 MPa, and the phenomenon of sticking to the steel plate was observed at different hot pressing temperatures. The results are shown in Table 1.
[0026] Table 1
[0027] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the high temperature resistant BOPP film for the copper clad laminate prepared by the present invention does not stick to the steel plate during hot pressing and has good high temperature resistance.
[0028] It can be seen from the data of Examples 1-3 and Comparative Examples 1-2 that the secondary treatment allows the polydimethylmethylhydrogensiloxane to be bonded to the surface through hydrosilylation, thereby improving the overall thermal stability and protecting the internal polypropylene molecular chains, thereby preventing the steel plate from sticking at higher temperatures.
[0029] From the data of comparative examples 3 to 5 and the blank control BOPP film, it can be seen that ethyl acrylate has no obvious improvement on the thermal stability, while treatment with allyl dimethyl phosphate and diethyl maleate can significantly improve the thermal stability of the BOPP film, indicating that allyl dimethyl phosphate and diethyl maleate can cross-link the molecular chains of the BOPP film after light treatment through ester exchange reaction, making the overall structure tighter, so that it can be non-stick to the steel plate at a higher temperature.
[0030] Test Example 2 Tensile strength and flame retardancy tests Tensile strength test method: Test in accordance with GB / T 1040.3 standard.
[0031] Flame retardant performance test method: Tested in accordance with GB / T 2406. The results are shown in Table 2.
[0032] Table 2
[0033] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the high temperature resistant BOPP film for copper clad laminate prepared in the present invention has good tensile strength and flame retardant properties.
[0034] By comparison, the tensile strength and limiting oxygen index of Comparative Example 1 are low, indicating that ethyl acrylate cannot cross-link the BOPP film after light treatment, and cannot improve the flame retardancy compared with allyl dimethyl phosphate.
[0035] By comparison, the limiting oxygen index of comparative example 2 is low, which indicates that diethyl maleate cannot improve the flame retardancy compared with dimethyl allyl phosphate.
[0036] By comparison, the tensile strength and limiting oxygen index of Examples 3 to 5 are low, indicating that the secondary treatment allows polydimethylmethylhydrogensiloxane to be bonded to the surface through hydrosilylation, which can improve the flame retardant properties, and polydimethylmethylhydrogensiloxane can also cross-link double bonds on different molecular chains through hydrosilylation, further improving the tensile strength.
[0037] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A high temperature resistant BOPP film for copper clad laminate, characterized in that: The high temperature resistant BOPP film for copper clad laminate is prepared by subjecting the BOPP film to light treatment and then sequentially treating it with a primary treatment liquid and a secondary treatment liquid.
2. A high temperature resistant BOPP film for copper clad laminate according to claim 1, characterized in that: The light treatment is to wash the BOPP film and immerse it in an aqueous solution of ammonium sulfate, take it out and irradiate the surface with ultraviolet light, then take it out and irradiate the other side with ultraviolet light, and finally soak it in water.
3. A high temperature resistant BOPP film for copper clad laminate according to claim 2, characterized in that: The primary treatment liquid is prepared by uniformly mixing allyl dimethyl phosphate and anhydrous ethanol; the secondary treatment liquid is prepared by uniformly mixing polydimethylmethylhydrogensiloxane, chloroplatinic acid and n-hexane.
4. A method for preparing a high temperature resistant BOPP film for a copper clad laminate, characterized in that: The method comprises the following preparation steps: (1) Light treatment: The BOPP film was ultrasonically cleaned with pure water and anhydrous ethanol for 10-15 min in sequence, and dried at 60-70°C for 3-4 h to obtain the cleaned BOPP film. The cleaned BOPP film was immersed in an aqueous solution of ammonium persulfate with a mass fraction of 20%-30%, and taken out after standing for 10 min. The film was drained until no liquid droplets fell for 5 s, spread flat and subjected to ultraviolet irradiation, and immersed in an aqueous solution of ammonium persulfate with a mass fraction of 20%-30% again. The film was taken out after standing for 10 min, and drained until no liquid droplets fell for 5 s. The film that had not been subjected to ultraviolet irradiation was subjected to the same ultraviolet irradiation, and ultrasonically cleaned with pure water and anhydrous ethanol for 10-15 min in sequence, and then immersed in pure water at 40-50°C for 16-20 h. The film was taken out and dried at 60-70°C for 6-8 h to obtain the BOPP film after light treatment. (2) Primary treatment: The light-treated BOPP film was immersed in the primary treatment liquid and allowed to stand for 30 to 60 minutes. The film was taken out and drained until no liquid dripped for 5 seconds. The film was placed in a muffle furnace for heating treatment. The film was kept at 70 to 80°C for 20 to 30 minutes, 100 to 110°C for 20 to 30 minutes, and 140 to 150°C for 50 to 60 minutes. After cooling to room temperature, the film was immersed in the primary treatment liquid and then placed in a muffle furnace for heating treatment for three times. After cooling to room temperature, the film was ultrasonically cleaned with pure water and acetone for 10 to 15 minutes, and dried at 60 to 70°C for 6 to 8 hours to obtain a BOPP film after primary treatment. (3) Secondary treatment: Immerse the BOPP film after the primary treatment in the secondary treatment solution and let it stand for 10-15 minutes, take it out and drain it until no liquid drops for 5 seconds, let it stand at 70-80℃ for 30-40 minutes, cool it to room temperature, and then repeat the process of immersing it in the secondary treatment solution and letting it stand at 70-80℃ for 30-40 minutes for three times. After cooling to room temperature, ultrasonically clean it with pure water and acetone for 10-15 minutes in turn, and dry it at 60-70℃ for 6-8 hours to obtain a high-temperature resistant BOPP film for copper clad laminate.
5. The method for preparing a high temperature resistant BOPP film for copper clad laminate according to claim 4, characterized in that: The BOPP film thickness in step (1) is 38 μm.
6. The method for preparing a high temperature resistant BOPP film for copper clad laminate according to claim 4, characterized in that: The process parameters of the ultraviolet irradiation in step (1) are: ultraviolet wavelength 254nm, light intensity 9000μw / cm 2 , illumination time 2min.
7. The method for preparing a high temperature resistant BOPP film for copper clad laminate according to claim 4, characterized in that: The primary treatment liquid in step (2) is prepared by uniformly mixing allyl dimethyl phosphate and anhydrous ethanol in a mass ratio of 1:4-6.
8. The method for preparing a high temperature resistant BOPP film for copper clad laminate according to claim 4, characterized in that: The secondary treatment liquid in step (3) is prepared by uniformly mixing polydimethylmethylhydrogensiloxane, chloroplatinic acid and n-hexane in a mass ratio of 1:0.02-0.03:6-8.